(3NHGjG GdRhGjGs - (3MSf Hf Ydj Hf jMji, CHh GdHbGA GdYLjej,J (B1113 (3g` s ((3GdTjN eMeO aJMi Gddg Gdbehdi GdeOfi s)
(3ChdgG (B:s
(3HYO GdOjHGLg(B: (3CeG HYO aEfi deG ef Gddg Yi HLeY gPG GdcJGH GdeHGQc s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B205 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B264s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B537 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B120 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs